2014
DOI: 10.1038/jid.2013.284
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Filaggrin Is Internalized and Processed to Correct Filaggrin Deficiency

Abstract: This study was designed to engineer a functional filaggrin (FLG) monomer linked to a cell-penetrating peptide (RMR) and to test the ability of this peptide to penetrate epidermal tissue as a therapeutic strategy for genetically determined atopic dermatitis (AD). A single repeat of the murine filaggrin gene (Flg) was covalently linked to a RMR motif and cloned into a bacterial expression system for protein production. Purified FLG+RMR (mFLG+RMR) was applied in vitro to HEK-293T cells and a reconstructed human e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 33 publications
0
28
0
5
Order By: Relevance
“…Topical treatments which restore the skin barrier in AD are an important modality in the armory against AD. Incorporation of recombinant filaggrin monomers is one approach currently being tested in animal models (115). As we learn more about the skin barrier and its defects in AD, we can anticipate new developments in topical therapies for this debilitating disease.…”
Section: Discussionmentioning
confidence: 99%
“…Topical treatments which restore the skin barrier in AD are an important modality in the armory against AD. Incorporation of recombinant filaggrin monomers is one approach currently being tested in animal models (115). As we learn more about the skin barrier and its defects in AD, we can anticipate new developments in topical therapies for this debilitating disease.…”
Section: Discussionmentioning
confidence: 99%
“…There is now emerging evidence that physiologic lipids, if delivered in sufficient quantities, and at appropriate molar ratios, are effective in the treatment of even moderate-to-severe AD, without any of the safety concerns surrounding glucocorticoids and immunomodulators 108* . Alternatively, those patients with AD due to either single-allele mutations in FLG , and/or acquired reductions in FLG, become potential candidates for strategies that either upregulate FLG expression 128129 ; or enhance the transdermal delivery of FLG monomers to deficient skin 129 . Yet, it must be noted that the latter approach, though very elegant in theory, may not be practical for a generalized disease such as AD.…”
Section: Conclusion: Clinical and Therapeutic Implicationsmentioning
confidence: 99%
“…A recent study demonstrated that JTC801, a new synthetic compound, increased filaggrin expression in human keratinocytes in vitro and decreased the development of AD-like lesions in mice in vivo [102]. The importance of barrier strengthening therapy is supported by the outcome that a topical recombinant filaggrin delivery through cell penetrating peptide could restore the AD-like inflammation in filaggrin knockout mice [103]. Defects of tight junction proteins, such as claudin, could have a permissive effect on the entry of irritants, allergens or pathogens into the epidermis [33,104].…”
Section: Barrier Dysfunctionmentioning
confidence: 99%